The accessibility of fitness centers for people with disabilities: A systematic review. Issue 4 (October 2018) - Calder, Allyson; Sole, Gisela; Mulligan, Hilda
Abstract: Background: Fitness centers could be ideal places for people with disabilities to engage in the recommended levels of physical activity for healthy well-being. However, one of the primary barriers to participation at fitness centers is an inaccessible built environment. Objective: This review study aimed to evaluate the accessibility of public indoor fitness centers for people with disabilities. Methods: We searched electronic databases and web based search engines using keywords and synonyms for fitness centers, people with disability and accessibility. Observational studies that used standardized measures to evaluate fitness centers were included and critically appraised using a modified version of the checklist for randomized and non-randomized studies developed by Downs and Black. We analyzed the data descriptively. This systematic review protocol is registered in PROSPERO (ID:CRD42016043945). Results: A total of 533 fitness centers were evaluated for accessibility across 14 studies. Ten (85%) of the 14 studies were undertaken in the United States of America. Instruments (n = 2) used to evaluate fitness centers were based on the Americans with Disabilities Act compliance legislation and measured domains of physical access (e.g., bathrooms, equipment, parking) and system access (e.g., policies, programs, professional behavior). We calculated weighted percentage mean scores per accessibility domain. The least accessible domain was "hot tubs/whirlpools/saunas/steam rooms" at 33%, with "programs" being the most accessible domain at 68%. Conclusions: Fitness center accessibility for people with disabilities remains poor. Adopting the principles of universal design in legislation would achieve equitable access for all, thereby allowing people with disabilities to participate actively in their communities with dignity and autonomy.